Effectiveness of Waste Activated Sludge Solubilization Treated by Sonication, Thermal and Acid-Alkali Adjustment - Wang, Xiaoxia; Lu, Shuguang; Qiu, Zhaofu; Ying, Weichi (Asian Journal of Chemistry, 2014)
Solubilization performance using sonication, thermal and acid-alkali adjustment in batch treatment of waste activated sludge (WAS) samples were evaluated. By sonication, the organics (measured as COD) and nutrient releases from waste activated sludge increased with treatment time (up to 60 min) and intensity (0.167, 0.330 and 0.500 W/mL); while, by thermal treatment, the releases increased with treatment time (up to 3 h) and temperature (50, 70 and 90 ºC). Organic-N of the supernatant accounted for most of the total nitrogen released from the waste activated sludge, followed by NH3-N and trace amounts of nitrate and nitrite; orthophosphorus. was the predominant form of the released total phosphorus. The molecular weight distribution of soluble organics, BOD5/COD and C/N data of the supernatant suggest that it can be returned to the biological aerobic unit for treatment without any negative effect. The sludge treatment by adjusting pH to 3-10 was unable to cause substantial release of organic and nutrient species; at a higher pH of 12 for 4 h, the releases were still too few to result in a significant reduction of the waste activated sludge volume. Among the three treatments, sonication shows an attractive process for waste activated sludge solubilization.